2012
DOI: 10.1136/jnnp-2012-302272
|View full text |Cite
|
Sign up to set email alerts
|

Japanese amyotrophic lateral sclerosis patients with GGGGCC hexanucleotide repeat expansion in C9ORF72

Abstract: C9ORF72 repeat expansions were present in a Japanese cohort of ALS patients, but they were rare. Intriguingly, Japanese patients appear to carry the same risk haplotype identified in white populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 13 publications
(29 reference statements)
2
46
1
2
Order By: Relevance
“…Similar rates are reported for the association between C9ORF72 and fronto-temporal dementia (FTD), linking to the same gene 2 apparent distinct phenotypes. The prevalence of C9ORF72 in ALS cases is much lower in East (less than 4% in Japan) [32] and South Asia (5.9% among familial and 1.6% among sporadic in Iran) [33]. Behavioral clinical features are more common in ALS and FTD with C9ORF72 mutation.…”
Section: C9orf72 and Geographic Spreading Of Genetic Riskmentioning
confidence: 99%
“…Similar rates are reported for the association between C9ORF72 and fronto-temporal dementia (FTD), linking to the same gene 2 apparent distinct phenotypes. The prevalence of C9ORF72 in ALS cases is much lower in East (less than 4% in Japan) [32] and South Asia (5.9% among familial and 1.6% among sporadic in Iran) [33]. Behavioral clinical features are more common in ALS and FTD with C9ORF72 mutation.…”
Section: C9orf72 and Geographic Spreading Of Genetic Riskmentioning
confidence: 99%
“…However, the reported frequencies in Asian samples have been lower. Four studies have reported a low frequency of HRE in Japanese ALS cases (0 -3.4% in fALS, and 0.4% sALS) [73,78,129,130] and a higher frequency was reported in cases from Taiwan of Han Chinese ancestry (18.2% in fALS, and 2.0% in sALS) [75]. In the present study, the author reports that the frequency of the C9orf72 HRE in Chinese sALS patients is 0.3%.…”
Section: Discussionsupporting
confidence: 45%
“…To date, this is the largest cohort screened in non-Caucasian ALS cases. Previous reports about C9orf72 HRE in different populations support the hypothesis that the pathogenic HRE arose from a single founder haplotype both in Caucasian and Asian populations [11,73,75,78,80,81,129,130], although for cases in Taiwan it was postulated that the HRE was introduced in the 17 th century when Taiwan was under Dutch and Spanish colonial rule. The conjecture that Asian HREs arose on the same European founder seems inconsistent with the mutation occurring in a founder 1,500 years ago [78].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, FTLD or ALS associated with chromosome 9 open reading frame 72 (C9ORF72) hexanucleotide expansion exhibits pathological aggregation of TDP-43 and, in some cases, low penetration, 20,21 although these mutations are extremely rare in Japan. 22 It was recently reported that the pattern of ubiquilin abnormalities in ALS and FTLD corresponds well with the presence of C9ORF72 hexanucleotide expansion. 23 The UBQLN-2-positive, p62-positive, but TDP-43-negative thick dystrophic neurites are abundantly present in patients with C9ORF72 hexanucleotide expansion, predominantly in the hippocampus and cerebellum.…”
Section: Immunohistochemical Screening Of Hexanucleotide Repeat Expanmentioning
confidence: 97%